Post-operative outcomes and quality of life assessment after thoracoscopic lobectomy for Non-small-cell lung cancer in octogenarians: Analysis from a national database. (June 2021) - Bongiolatti, Stefano; Gonfiotti, Alessandro; Borgianni, Sara; Crisci, Roberto; Curcio, Carlo; Voltolini, Luca; ,; Alloisio, Marco; Amore, Dario; Ampollini, Luca; Andreetti, Claudio; Argnani, Desideria; et al.
Abstract: Background: Thoracoscopic lobectomy (VATS-L) for non-small-cell lung cancer (NSCLC) is a well-established option for early stage NSCLC, but the evidences are limited for octogenarians. Objective: The objectives of this multi-institutional study were to evaluate the post-operative outcomes of VATS-L in octogenarians and to estimate the post-operative quality of life (QoL) using a validated questionnaire (EuroQoL5D). Methods: Data from patients underwent VATS-L between 2014 and 2019 were analysed and divided into two groups: Group A (younger patients) and Group B (octogenarians). To define predictors for complications, univariate and multivariable logistic regression analysis were performed. Results: 7023 patients underwent VATS-L and 329 (4.6%) were octogenarians. 30-day and 90-day post-operative mortality were similar (0.95% vs 0.91%, p = 0.84 and 1.3% vs 1.2%, p = 0.58), whereas the percentage of patients who suffered from any complication (25.5% vs 31.9%, p = 0.012) and the complication rate (31.6% vs 45.2%, p=<0.01) were higher for octogenarians. At discharge, the values of EuroQoL5D were worse in group B, but after one month these levels became similar. Age >80 years had a significant influence on morbidity on both univariate and multivariable analyses (p = 0.025). Conclusions: VATS-L for NSCLC can be performed in selected octogenarians without increased risk of post-operative death, acceptable not-life-threatening complications and a moderate impact on QoL. Highlights: What are the outcomes thoracoscopic lobectomy for non-small-cell lung cancer? What is the impact of VATS-lobectomy on Quality of Life (QoL) in octogenarian patients? Post-operative complications were significantly more frequent, but not life-threatening. Levels of QoL were worse for elderly patients, but after a month these levels became similar. VATS-lobectomy can be safely performed in selected octogenarians, without worsening their QoL.